MANAJEMEN BAJA TULANGAN DENGAN METODE JUST IN TIME DENGAN KOMBINASI BAR BENDING SCHEDULE (STUDI KASUS PROYEK PEMBANGUNAN GEDUNG X PROVINSI JAWA BARAT) - Atania Qatrannada; Faris Fadhlurrahman; Rahmi Hidayati; Merley Misriani; Desmon Hamid (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
The application of material management, especially reinforcing steel is very important because it can determine the success of a construction project. This study uses data on the X building construction project such as DED, schedule, and logistics data. The purpose of this study was to analyze the application of reinforcing steel management using the Just In Time method. In calculating the quantity of reinforcing steel in this study, assisted by the Bar Bending Schedule. The results of the analysis obtained the quantity of reinforcing steel for the 3rd floor is for D10 as many as 5888 bars, D13 as many as 539 rods, D16 as many as 2176 rods, D19 as many as 1363 rods, D22 as many as 772 rods, and D25 as many as 51 rods. As for the 4th floor, there are 5740 bars of D10 steel, 525 bars of D13, 2012 of D16, 1359 of D19 88, 732 of D22, and 49 of D25. After calculating the cost, we get the cost of reinforcing steel for the 3rd floor is Rp1,380,376,857.80 and for the 4th floor is Rp1,333,301,299.20. This study concludes that the Just In Time method can be applied in reinforcing steel management which is adapted to the characteristics of the X building project. In addition, the use of a bar bending schedule is very effective and efficient compared to the conventional method of planning the use of the remaining pieces of reinforcing steel so that it can be profitable in terms of time.